Experimental and numerical studies of fixed-ended cold-formed stainless steel equal-leg angle section columns - Zhang, Lulu (2021)
The flexural-torsional buckling behaviour of fixed-ended cold-formed stainless steel equal-leg angle section columns was experimentally and numerically investigated in this paper. The testing programme was conducted on two press-braked austenitic stainless steel equal-leg angle sections, and involved material testing, initial imperfection measurements and sixteen fixed-ended column tests. The test setup and procedure, together with the key experimental results, load–mid-height torsional rotation histories and flexural-torsional buckling failure modes, were fully reported. Finite element models were then developed to simulate the fixed-ended cold-formed stainless steel equal-leg angle section column tests, and the numerical structural responses and failure modes were shown to match well with the corresponding experimental observations. The validated finite element models were then utilised to carry out parametric studies to generate an extensive pool of numerical data on fixed-ended cold-formed stainless steel equal-leg angle section columns susceptible to flexural-torsional buckling. The load-carrying capacities derived from both the experiments and FE modelling were compared with the resistance predictions from the established design standards in Europe, America, and Australia/New Zealand and a recently proposed direct strength method. The comparison results generally indicated that the existing design codes unduly underestimate the flexural-torsional buckling resistances of fixed-ended cold-formed stainless steel equal-leg angle section columns, while the direct strength method substantially improves the design accuracy on average, but with many overpredicted resistances, indicating that further improvements are generally required.